2014
DOI: 10.1590/abd1806-4841.20143008
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy assisting the diagnosis of mycetoma: case report and literature review

Abstract: Mycetomas are a chronic skin infection characterized by perilesional edema, formation of sinus tracts, and discharge of purulent or seropurulent exudate containing grains. This report aims to demonstrate the clinical diagnosis (by dermoscopy) of a skin lesion that initially bared no clinical features of a mycetoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 1 publication
(1 reference statement)
1
16
0
Order By: Relevance
“…Sudan appears to have the highest number of cases per capita of any country in the world . Most cases of mycetoma occur in India, Mexico, Sudan and Venezuela, although there are reported cases in other countries such as Argentina, Brazil, Iran and Somalia . Sporadic cases have also been reported in countries with mild weather .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudan appears to have the highest number of cases per capita of any country in the world . Most cases of mycetoma occur in India, Mexico, Sudan and Venezuela, although there are reported cases in other countries such as Argentina, Brazil, Iran and Somalia . Sporadic cases have also been reported in countries with mild weather .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Most cases of mycetoma occur in India, Mexico, Sudan and Venezuela, [3][4][5] although there are reported cases in other countries such as Argentina, Brazil, Iran and Somalia. [6][7][8][9][10] Sporadic cases have also been reported in countries with mild weather. 11 In Venezuela few cases of mycetoma have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…74,75 Mycetoma is clinically characterized by papules, nodules, perilesional edema, formation of sinus tracts, and discharge of purulent exudate containing grains (Figure 7). 76 In some publications, it has been reported that it occurs more frequently in men than in females. It is most commonly seen on the foot.…”
Section: Deep Fungal Infectionsmentioning
confidence: 99%
“…Dermoscopy is an easy, quick, and noninvasive tool widely used in the diagnosis of skin tumors. Recently, its use extended to the field of infectious skin diseases . Dermoscopy is helpful in visualizing minute grains (Fig.…”
mentioning
confidence: 99%
“…Recently, its use extended to the field of infectious skin diseases. 2 Dermoscopy is helpful in visualizing minute grains ( Fig. 2a).…”
mentioning
confidence: 99%